Client Satisfaction towards Quality of Health Services: An Assessment at Primary Healthcare of District Gujranwala - Kauser Aftab Khan; Shahzad Ali Khan; Zubia Qureshi; Moazzam Ali Khan; Fouzia Nadeem Gill; Mudassar Mushtaq Jawad Abbasi (International Journal of Public Health Science (IJPHS), 2017)
This survey designed to evaluate the satisfaction level and the factors that affect the patient satisfaction regarding health care delivery services with the aim to improve the services in the primary health care settings of Gujranwala. A Cross Sectional Study done on randomly selected patients attending the basic health units of Gujranwala, with more than18 years of age. Pretested structured "Liker scale questionnaire" was used for data collection. Out of total respondents, 62 (41.3%) clients were satisfied with the services provided by the basic health units of Gujranwala. The factors identified to determine patient satisfaction were accessibility of services, behavior of staff, health education, level of cleanliness, drug availability and miscellaneous services. Not a single ranked area of satisfaction noticed. Client’s occupation and income had significant relationship with the patient satisfaction level. Gender, age, and education of clients were not contributing factors; they not affect the client satisfaction level.Less than half clients were satisfied with the services provided by the basic health units. Management of health facilities needs to improve the services.